Willingness to participate in combination screening for lung cancer, chronic obstructive pulmonary disease and cardiovascular disease in four European countries - Behr, Carina; Koffijberg, Hendrik; IJzerman, Maarten; Kauczor, Hans-Ulrich; Revel, Marie-Pierre; Silva, Mario; Stackelberg, Oyunbileg von; van Til, Janine; Vliegenthart, Rozemarijn (European radiology, 2024)
Lung cancer screening (LCS), using low-dose computed tomography (LDCT), can be more efficient by simultaneously screening for chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD), the Big-3 diseases. This study aimed to determine the willingness to participate in (combinations of) Big-3 screening in four European countries and the relative importance of amendable participation barriers.
Gesehen am 10.04.2024